ANALISIS BREAK EVENT POINT PADA PT. HOLLY KADOZ NIASINDO - Fau, Samanoi Halowo; Waoma, Samalua (Balance: Jurnal Riset Akuntansi dan Bisnis, 2022)
The purpose of this study was to determine the break-even point of sales of the company PT. Holly Kadoz Niasindo. The type of research used in this study is qualitative research with a descriptive approach. The subjects in this study were PT. Holly Kadoz Niasindo. Meanwhile, the object of this research is the financial statements of PT. Holly Kadoz Niasindo which consists of reports on costs, and total production for several times carrying out operations in the production calendar. The number of sales each month is fluctuating and it is not even possible to ascertain whether there are many or not every month. The difference in production volume is caused by changes in the total demand for Kakaz cups so it can affect the number of fixed costs and variable costs used by the company. In this study, the average value of the break-even point during the analysis was 11,934 Kazadz cups or Rp. 214.815,000 (Two hundred and fourteen million eight hundred and fifteen thousand rupiah). Profit is determined by the number of products produced. In this study, the number of Kazaz cups produced for 12 (twelve) months was 180,000 (one hundred and eighty thousand) boxes or Rp. 3.240,000,000 (Three billion two hundred and forty million rupiah). Earnings profit every month also fluctuates so that the company's average profit can be calculated during the analysis of Rp. 278.500.000 (Two hundred seventy-eight million five hundred thousand rupiahs)